NURSING CARE OF HYPERTHERMIA IN CHILDREN FEBRILE SEIZURES: A CASE REPORT - Tyas, Anestasia Pangestu Mei; Rosa , Lailatul Fitria; Mardhika , Amellia; Sulpat , Emuliana; Fadliyah, Lailatul; Susanto , Joko; Ilkafah, Ilkafah (Journal of Vocational Nursing, 2023)
Introduction: Febrile seizures occur due to increased temperature due to extracranial processes. There is a predisposition Familial and more common in boys than girls. Prolonged and repeated attacks can cause severe disturbances in the child's brain, so the child has a mental disability. This case study aims to apply hyperthermia nursing care for children with febrile seizures in the pediatric inpatient room at Lamongan Hospital. Methods: The research design used is to study cases with a nursing care approach. The sample in this study was one child patient with febrile seizures: data collection techniques using interviews, observation, documentation studies, and physical examination. The research instrument used the pediatric nursing care assessment format. Results: After implementing nursing for 3x24 hours, the nursing diagnosis of hyperthermia is resolved. The risk of injury does not occur during the treatment period because the body temperature has reached 36.5 0 C, and the patient has never had another seizure. Conclusions: It is necessary to collaborate with professional care providers and family participation for the success of nursing care according to nursing care standards to prevent happening seizures repeated.